Conhecimentos e atitudes dos médicos generalistas das unidades básicas de saúde da cidade de São Paulo frente a pacientes com demência - Steiner, Ana Beatriz Quintes [UNIFESP] (2018)
Objectives: To describe the knowledge and attitudes of the general practitioners of the primary health care network in the city of São Paulo in relation to patients with dementia and to identify which medical standards of attitudes are associated with greater knowledge about the subject. Methods: Ten percent of the basic health units of the city of São Paulo (N = 45), distributed proportionally in 6 Regional Health Coordination Units, were randomly selected to collect data. Interviews were planned with the two general practitioners who worked in each unit, obtaining a total of 81 physicians interviewed from the 90 predicted (9 refusals); they answered the transculturally translated version of the Brazilian questionnaire for 2 British questionnaires, the Knowledge Quiz and the Attitude Quiz (attitudes towards the demented patient), as well as a sociodemographic and occupational questionnaire for understanding the profile of general practitioners working in primary care. A descriptive analysis of data, the factor analysis of the main components of the Attitude Quiz and the study of association between attitudes and knowledge plus the multiple linear regression test were carried out to determine the relation between the occupational and knowledge profile in dementia over the patterns of attitudes. Results: The physicians interviewed had a median time of 5 years of graduation (range 1 to 45 years); only 35.8% of them worked exclusively with primary care and less than 40% had completed or were in medical residency or equivalent specialization. The physicians showed a lower knowledge in the diagnosis of dementia in relation to the epidemiology of the disease and its therapeutic management (p <0.001). Their attitudes towards demented patients resulted in 4 factors explaining 63.2% of the total variability of the items: proactive optimist (doctors' perception that they can contribute to the life quality of the elderly with dementia and that they are willing to it, delegate attitude (perception that the management of the elderly with dementia can be done with optimism, but they do not take responsibility for it and delegate to other instances: α = 0.47), implicit discouragement (doctors do not perceive themselves as pessimistic in the care of the elderly, but they place in the family the difficulty of seeing the future in the management of the elderly with dementia as if they were discouraged, α = 0.26) and the explicit discouragement (doctors have the clear perception that any management of them with the elderly with dementia will be fruitless; α = 0.47). The regression study showed that the attitude of explicit discouragement decreases the greater the weekly workload of the physician in the units, and that the optimistic delegate attitude of the physician decreases in the same situation, but also if the diagnosis of dementia is greater and if this doctor has completed residency or specialization. Conclusion: The lack of experience of physicians working at the UBS in São Paulo, with little training in recognition of cognitive alterations in the elderly, impairs the diagnostic recognition of dementia in the elderly and favors discouragement attitudes among professionals. Investment in training in the form of continuing education and in stimulating medical residency or equivalent specialization are key to improve professional performance in the field of dementia in primary care.